Insights from an expressive writing intervention on Facebook to help alleviate depressive symptoms. (September 2016) - Lee, Sang Won; Kim, Inyeop; Yoo, Jaehyun; Park, Sungkyu; Jeong, Bumseok; Cha, Meeyoung
Abstract: Depression is one of the most common mental disorders. Studies have shown that various online social network (OSN) activities can be used as a marker for people's moods as well as symptoms of subsyndromal depression, suggesting possibilities for online-based interventions. This study investigates one such potential by developing an expressive writing application within Facebook and by investigating how the designed intervention as well as various online social network activities contribute to improving one's emotional state. Experimental data show that negative emotional words and cognitive words in online expressive writing are the two most important factors in alleviating depressive symptoms. Furthermore, participants who have had previous experience expressing emotions in OSNs reported the greatest reduction in depressive symptoms. Our findings have implications that can assist in designing personalized online intervention platforms and for sophisticated writing therapy to maximize the effect of expressive writing. Highlights: We developed a web-based intervention platform for expressive writing. Emotional and cognitive words on intervention were related to recovery of depression. Previous writing tendency may affect the choice of words during intervention. The platform is effective to people who are familiar with expressing emotions on OSNs. This study helps understand the beneficial effects of web-based expressive writing.